Proceedings of the 2023 International Conference on Wireless Communications, Networking and Applications - Siarry, Patrick; Jabbar, M. A; Cheung, Simon King Sing; Li, Xiaolong (Lecture Notes in Electrical Engineering, 2025)
This open access book includes original, peer-reviewed research papers from the 2023 International Conference on Wireless Communications, Networking and Applications (WCNA 2023), held in Shenzhen, Guangdong, China, from December 29 to 31, 2023. The topics covered include but are not limited to: Wireless Communications; Devices, Tools, and Techniques for WSN and Other Wireless Networks; Wireless Sensor Networks; Internet of Things (IoT); AI; Signal Processing; and Sustainable Pervasive WSN Applications. The papers showcased here share the latest findings on Wireless Communications, Networking and Applications, making the book a valuable asset for researchers, scientists, scholars, engineers and students from the universities all around the world and the industry.